Apoptosis Induction of K562 Cells by Lymphocytes: An AFM Study. Issue 1 (15th February 2013) - Jin, Hua; Zhao, Hongxia; Liu, Li; Jiang, Jinhuan; Wang, Xiaoping; Ma, Shuyuan; Cai, Jiye
Summary Antitumor immunotherapies, as a prospective approach for local cancer treatment, are attracting increasing interests. To detect the reacting course of immune and tumor cells, we have observed the process of K562 cells (a human erythroleukemic cell line) coculturing with peripheral lymphocytes, and the morphological and ultrastructural alterations of K562 cells and lymphocytes were investigated as well using atomic force microscopy (AFM). AFM morphological imaging revealed that after coculture the apoptosis‐like structures such as blebbing, pores, and apoptotic bodies were observed on the K562 cells. Also, the cell‐surface roughness decreased significantly, which implied the changes in chemical composition of cell membranes. Moreover, the lymphocytes were damaged to some extent induced by the coculture. The data demonstrated that K562 cells could be attacked and induced apoptosis by lymphocytes, and they would make damages to lymphocytes to escape the surveillance of immune system. SCANNING 35:7‐11, 2013. © 2012 Wiley Periodicals, Inc.